Restless legs syndrome: an underappreciated and distressing problem for haemodialysis patients. Issue 10 (October 2014) - Chu, L.; Chu, E.; Dogra, G.; Chakera, A.
Abstract Restless legs syndrome is a distressing condition that is more common in patients with end‐stage renal failure. Despite the significant impact it has on quality of life and the documented association between restless legs syndrome and increased mortality, limited data regarding the epidemiology of restless legs syndrome in Australian dialysis patients are available. We report a prospective study that assessed the prevalence and factors associated with restless legs syndrome in an in‐centre haemodialysis population.